Bioremediation of Pb and Cd contaminated soil using microorganism - Andriyani Dea Wulandari; Vincentia Irene Meitiniarti (Faculty of Science and Mathematics, Universitas Kristen Satya Wacana, 2021)
The increase in industrial waste, especially those containing Pb and Cd, which is discharged into the environment results in more polluted environment conditions. Polluted enviornment is very dangerous for the survival of living things. This technique use living things to reduce environmental pollution, making it safe for living things. Bioremediation can be carried out by in-situ and ex-situ methods with several bioremediation mechanisms, including biosorption, bioaccumulation, bioleaching, and bioprecipitation. The use ex-situ techniques in bioremediation is easier to do, especially if it is carried out to remediate soils under controlled conditions in the laboratory.